2004
DOI: 10.1093/jnci/djh217
|View full text |Cite
|
Sign up to set email alerts
|

Akt Phosphorylation and Gefitinib Efficacy in Patients With Advanced Non-Small-Cell Lung Cancer

Abstract: Patients with P-Akt-positive tumors who received gefitinib had a better response rate, disease control rate, and time to progression than patients with P-Akt-negative tumors, suggesting that gefitinib may be most effective in patients with basal Akt activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
260
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 353 publications
(287 citation statements)
references
References 30 publications
19
260
4
Order By: Relevance
“…Shah et al 40 reported that p-AKT1 was strongly correlated with well-differentiated tumors, and that p-AKT1 expression in non-small cell lung cancer was a favorable independent prognostic factor. In a study by Cappuzzo et al, 41 p-AKT1 was associated with bronchioloalceolar carcinoma, which is a well-differentiated form of adenocarcinoma, and p-AKT1 positivity was associated with a reduced risk of disease progression. Taken together, there are tumors with high p-AKT1 or p-MTOR expression that remain well differentiated, seldom metastasize, and thus are associated with a better survival.…”
Section: Discussionmentioning
confidence: 98%
“…Shah et al 40 reported that p-AKT1 was strongly correlated with well-differentiated tumors, and that p-AKT1 expression in non-small cell lung cancer was a favorable independent prognostic factor. In a study by Cappuzzo et al, 41 p-AKT1 was associated with bronchioloalceolar carcinoma, which is a well-differentiated form of adenocarcinoma, and p-AKT1 positivity was associated with a reduced risk of disease progression. Taken together, there are tumors with high p-AKT1 or p-MTOR expression that remain well differentiated, seldom metastasize, and thus are associated with a better survival.…”
Section: Discussionmentioning
confidence: 98%
“…Findings in preclinical and clinical studies have highlighted the activation status of the Akt protein (Cappuzzo et al, 2004;Sordella et al, 2004).Akt, a serine/threonine kinase acts downstream of EGFR to regulate many cellular processes, including cell survival, proliferation and growth, and is activated by phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…AKT kinase is efficiently induced by growth factors like EGFR ligands or by ionizing radiation through the EGFR-mediated activation of PI3K (28)(29)(30)(31). PI3K itself is a heterodimeric complex composed of an 85-kDa regulatory subunit and a 110-kDa catalytic subunit.…”
Section: Introductionmentioning
confidence: 99%